SOCIAL CONFLICTS IN CHURCH DEVELOPMENT IN KECAMATAN IBU SELATAN KABUPATEN HALMAHERA BARAT (STUDY OF CONFLICT RESOLUTION AMONG CITIZENS IN CHURCH DEVELOPMENT IN ADU VILLAGE) - Wance, Marno; Suhu, Bakri La; Girato, Marsel M (Universitas Muhammadiyah Jember, 2019)
The church conflict that occurred in Adu Village, South Ibu Subdistrict, West Halmahera Regency was caused by unjust church leadership. Conflicts in the construction of places of worship often lead to violence, attacks and sealing of houses of worship by the community. This study aims to determine the occurrence of social conflict between residents in the construction of church in Adu village and to find out the resolution of the conflict. This research uses descriptive qualitative research that can be understood as a series of procedures used in solving problems, namely the cause of conflict between residents related to the construction of church in Adu Village by investigating and describing research objects based on facts in the field. Data sources used are primary data and secondary data with data collection techniques namely observation, interviews and document analysis. The research findings show that the cause of conflict in church construction is because (1) the church leadership is no longer neutral in serving the community, for example when visiting a sick Adu village community, the church leader only visits one group while the other group is ignored, and (2) the regulations of church leaders regarding residents? responsibilities to the church such as the obligation for each person to contribute IDR 200,000 per year for church construction is considered too burdensome for the community. From the factors causing the conflict, conflict resolution is carried out by way of negotiations (consensus agreement) between the Old GMIH and the GMIH Renewal. From these negotiations, a mutual agreement ensued that the construction of a new church planned by the GMIH Renewal would continue.